Bacterial meningitis secondary to otomastoiditis by Providencia Rettgeri in private of liberty - Filho, Cezar Arruda de Oliveira; Pelucio, Isabela Pimenta; Bonini, Carolina Bertini; Nomura, Akissy Aline Uchiuama; de Oliveira, Ana Julia Fonseca Arruda; de Andrade, Eduardo Vilela; de Oliveira, Lazaro Leonardo Mendes; Pereira, Felipe Garcia; Colares, Philippe de Figueiredo Braga (Seven Editora, 2024)
Introduction: This case report describes a rare occurrence of meningitis caused by Providencia rettgeri in an inmate patient. Providencia rettgeri is a gram-negative bacterium that rarely causes meningitis, and is most commonly associated with urinary tract infections and septicemia in immunocompromised patients. (1)Case Presentation: Man, 29 years old, deprived of liberty, without comorbidities. Onset of otalgia, fever and otorrhea for 21 days, with previous use of Ceftriaxone + Oxacillin, without improvement. Admitted due to prostration for 02 days, mental confusion and lowering of the level of consciousness. Physical examination showed neck stiffness, ECG 9, left otoscopy with purulent secretion and opaque tympanic membrane with central perforation of 10%. A CT scan suggestive of otomastoiditis was performed. In addition to the area of bone erosion in the posteromedial aspect of the ipsilateral mastoid, with communication with the cerebellar hemisphere determining peripheral edema. The cerebrospinal fluid was collected, antibiotic therapy for vancomycin + meropenem was scheduled, corticosteroid therapy was initiated, and the patient was referred for simple mastoidectomy on the left. It has been identified in the growth abscess culture of Providencia Rettgeri. Discussed with CCIH, we opted for maintenance of antibiotic therapy due to the patient's clinical severity and weekly cerebrospinal fluid control was suggested to determine the duration of treatment. After 28 days of treatment, the patient progressed with improvement in the CSF pattern, but developed bicytopenia. After 3 days of the end of treatment, the blood count showed improvement, the patient did not present motor or neurological sequelae, and was discharged from the hospital with outpatient follow-up.Comments: Providencia spp. is a genus composed of five species. In the clinical setting, P. stuartii is most commonly seen in patients. Most strains of P. rettgeri exhibit pathogenic properties similar to those of P. stuartii. In a literature review, there is a lack of data on CNS infection in humans by the species P. rettgeri (2). Deprived of liberty are often exposed to unhealthy environments that can predispose to the risk of contamination by atypical pathogens. We reinforce the importance of collecting cultures to increase our knowledge about these pathogens in this population and their resistance profiles, in order to optimize the conducts in the face of atypical cases such as the one reported. (3)Conclusion: This case highlights the importance of considering Providencia rettgeri as a potential pathogen in cases of meningitis, especially in at-risk populations such as inmates, opening the horizon for at-risk populations for this infection. Early identification and appropriate treatment are crucial for a favorable outcome, in addition to the need for further studies on the bacteria. DOI:https://doi.org/10.56238/sevened2024.018-026